FROM GLOBALIZATION TO INCULTURATION: Paradigm Shift in Negotiating the HIV/AIDS Dilemma in the African Context within the Framework of Fides et Ratio, art. 72 - Nwachukwu-Udaku, Benedict C (Asian Horizons, 2011)
To assert the global nature of HIV/AIDS is to state the obvious. Different studies and rationalities attest to the truth that HIV/AIDS does not have a well-defined geographically limited spread.1 The cosmopolitan nature of HIV/AIDS as seen in the statistics does not however undermine the fact that the effects of this sickness are not felt proportionally from one nation to another. This paper proposes to situate the local as a veritable site of empowerment for communities dealing with HIV/AIDS, as it is the case with the African continent.